A new porcine vascularized tibial bone allotransplantation model. Anatomy and surgical technique. Issue 2 (13th November 2017) - Kotsougiani, Dimitra; Willems, Joost I.; Shin, Alexander Y.; Friedrich, Patricia F.; Hundepool, Caroline A.; Bishop, Allen T.
Abstract : Introduction: Vascularized bone allotransplantation may provide new options for reconstruction of segmental defects if problems of long‐term immune modulation can be solved. The current literature lacks an orthotopic large animal model, limited to bone and without the confounding effects of other tissue types, permitting a multifaceted evaluation before new methods are used clinically. The purpose of this study was to develop a large animal model for vascularized bone allotransplantation. Materials and methods: Eight porcine hind limbs were dissected. Length, diameter, and location of all hindlimb vessels were measured and a single nutrient vessel supplying the tibial diaphysis identified enabling its use as a vascularized bone allotransplant. Four Yucatan minipigs were divided into two pairs with a major swine leukocyte antigen mismatch. A 3.5 cm tibial segment including its nutrient pedicle was raised simultaneously from each pig and transplanted into the matched defect of the other animal. Microarterial anastomosis of the pedicle and 3‐drug immunosuppression maintained VCA viability. Bone healing and limb function were followed for 16 weeks. Results: A consistent tibia diaphyseal nutrient artery arose from the caudal tibial artery to enter bone a mean 2.8 mm distal to the tibial tubercle with a pedicle length of 6.6 ± 3.3 mm and diameter of 1.6 ± 0.2 mm. Using this pedicle, we reconstructed a 3.5 cm tibial defect with a vascularized bone allotransplant in four animals. Immediate weightbearing as well as progressive bone healing was demonstrated. Conclusion: We have developed a vascularized tibial bone allotranplantation large‐animal model suitable for future bone‐only allotranplantation research in mini‐pigs.